Theological dictionary of the Old Testament ; v. II - Botterweck, G. Johannes; Ringren, Helmer, 1917-; Willis, John T. (Grand Rapids, MI Eerdmans, 1977)
Contents : v. II : bdl - galah Includes bibliographical references.
Translated from Theologisches Worterbuch zum Alten Testament Band IV, Lieferungen 5-9 published 1983-84 by Verlag W. Kohlhammer GMBH, Stuutgart, W. Germany.
Keywords: Bible. O.T. -- dictionaries -- Hebrew; Hebrew language -- dictionaries -- English